Level of Urbanization and Renewable Energy Consumption: The Case of Azerbaijan and Türkiye - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2024)
Conventional energy consumption requires serious costs, especially for countries that import this type of energy. In this study, one of the countries included in the analysis is considered as energy exporting countries and the other as energy importing countries. The study attempted to measure the relationship between urbanization levels and renewable energy consumption in Türkiye and Azerbaijan for the period 2000-2020. Granger causality test was applied to measure the effect of the relationship between variables in these countries. After the necessary assumption tests were applied, the analysis was started. According to the Granger test results, no causal relationship was found between the variables in both countries.